Tinjauan Atas Penyelenggaraan Standarisasi Pelayanan Ramah Anak di Puskesmas Balai Agung Kabupaten Musi Banyuasin - Yanti Safitri (Equivalent : Journal of Economic, Accounting and Management, 2026)
Child rights fulfillment services aim to ensure that every child feels safe, comfortable, and receives their basic rights optimally. As the first-line health service facility, Puskesmas plays a role in providing health services as well as shaping and changing the mindset and behavior of the community. Considering the local government's obligation to guarantee the fulfillment of children's rights and special protection through the development of Child-Friendly Districts/Cities (KLA), it is essential to implement Child-Friendly Services at Puskesmas (PRAP) as one of the indicators of the 5 (five) substantive clusters of the Convention on the Rights of the Child (KHA). The purpose of conducting the PRAP standardization process for Puskesmas Balai Agung is to obtain a picture of a standardized PRAP and to serve as a model for other puskesmas in implementing PRAP in Musi Banyuasin Regency. The PRAP assessment instrument consists of a series of indicators and/or parameters compiled in the form of a form, namely the Child-Friendly Services Requirements Form at Puskesmas. Puskesmas Balai Agung generally achieved high scores for the requested PRAP indicators. Going forward, efforts should be made to achieve improvements for child-friendly service standards in Musi Banyuasin Regency.   Abstrak  Layanan pemenuhan hak anak memiliki tujuan agar setiap anak merasa aman dan nyaman serta mendapatkan hak-hak dasarnya secara optimal. Puskesmas sebagai fasilitas pertama pelayan kesehatan memiliki peran pelayanan kesehatan serta membentuk dan mengubah pola pikir dan perilaku masyarakat. Menimbang kewajiban pemerintah daerah untuk menjamin terwujudnya pemenuhan hak dan perlindungan khusus anak melalui pengembangan Kabupaten/Kota Layak Anak (KLA) maka mutlak untuk diselenggarakan Pelayanan Ramah Anak di Puskesmas (PRAP) sebagai salah satu indikator dari 5 (lima) klaster substansi Konvensi Hak Anak (KHA). Tujuan dari diselenggarakannya proses standarisasi PRAP bagi Puskesnas Balai Agung adalah agar mendapatkan gambaran mengenai puskesmas yang terstandarisasi PRAP dan menjadi percontohan bagi puskesmas lain dalam penerapan PRAP di wilayah Kabupaten Musi Banyuasin. Instrumen penilaian PRAP berisi serangkaian indikator dan/atau perameter yang disusun dalam bentuk borang/ formulir yaitu Borang Persyaratan Pelayanan Ramah Anak di Puskesmas. Puskesmas Balai Agung secara umum mendapat skor yang tinggi untuk indikator-indikator yang diminta pada PRAP. Kedepannya agar dapat melakukan upaya perbaikan untuk tercapainya standar pelayan yang ramah anak di Kabupaten Musi Banyuasin.